A Computational Study of Anionic Alkoxide–Allene and Amide–Allene Cyclizations. Issue 46 (6th December 2017) - Cumine, Florimond; Young, Allan; Reissig, Hans‐Ulrich; Tuttle, Tell; Murphy, John A.
Abstract : Computational studies have been performed on potassium alkoxide‐allenes, as well as potassium and lithium amido‐allenes to probe the mechanism of their cyclizations to dihydrofurans and to 2, 5‐dihydropyrroles. A long‐standing proposal envisaged electron transfer from dimsyl anions (formed by deprotonation of the solvent DMSO) but this pathway shows an exceptionally high kinetic barrier, while direct 5‐ endo‐trig cyclization of the alkoxides and amides is much more easily achievable. The energy profiles for 4‐ exo‐trig cyclizations onto the allenes are also explored, and the preferred formation of the observed five‐membered products is rationalized. Abstract : Computational studies have been performed on alkali alkoxide‐allenes and as amido‐allenes to probe the mechanism of their cyclizations to dihydrofurans and 2, 5‐dihydropyrroles, respectively. The computations indicate that the reaction proceeds through a direct 5‐ endo‐trig cyclization. The energy profiles for 4‐ exo‐trig cyclizations onto the allenes are also explored.